Early Detection of Mycobacterium avium subsp. paratuberculosis Infected Cattle: Use of Experimental Johnins and Innovative Interferon-Gamma Test Interpretative Criteria - Corneli, Sara; Di Paolo, Antonella; Vitale, Nicoletta; Torricelli, Martina; Petrucci, Linda; Sebastiani, Carla; Ciullo, Marcella; Curcio, Ludovica; Biagetti, Massimo; Papa, Paola; Costarelli, Silva; Cagiola, Monica; et al. (Frontiers in Veterinary Science, 2021)
Paratuberculosis (PTB), also known as Johne’s disease, is a chronic proliferative enteritis of ruminants caused by Mycobacterium avium subsp. paratuberculosis (MAP). To date, PTB diagnosis, based on serology, faecal culture, and real-time polymerase chain reaction, has identified animals in advanced stages of infection. To detect MAP infection in animals earlier, the interferon-gamma (IFN-γ) test may be applied. This assay detects cytokines produced by T-lymphocytes of infected subjects after stimulation with purified protein derivatives (PPDs), extracted from Mycobacterium bovis (MB), and from Mycobacterium avium (MA). The study involved three bovine herds: one PTB-infected herd, one PTB-free herd, and one with an outbreak of bovine tuberculosis. The IFN-γ test was performed on 235 animals, using bovine purified protein derivative (PPDB), avian purified protein derivative (PPDA), and three experimental PPD Johnins (PPDJs) extracted from a synthetic liquid medium culture of MAP (PPDJ A, B, and C), to assess early MAP detection and avoid false reactions to MB. Furthermore, IFN-γ results were evaluated using 12 interpretative criteria (IC), based on the differences and ratio between PPDs optical density (OD) and IFN-γ basal OD values after lymphocytic stimulation. IC accuracy was expressed as area under the receiver operator characteristic curve. Through a longitudinal study, PPDJs proved to be specific and sensitive in the detection of MAP-infected animals. Among the evaluated ICs, six showed the best performance in terms of accuracy (p<0.0001), highlighting PTB subclinical infections. In particular, the two best criteria reached sensitivity values of 100% (confidence interval [CI] 95%, 94.1–100%) with a specificity of 91.8% (CI 95%, 81.9–97.3%) and sensitivity levels of 80.6% (CI 95%, 69.1–89.2%) with a specificity of 100% (CI 95%, 94.1–100%). Thus, the IFN-γ assay proved to be a useful diagnostic tool to identify early subclinical MAP-infected animals, in order to manage infected cattle or those exposed to MAP and to monitor younger calves within a herd. Furthermore, the IFN-γ test can be considered an additional test to avoid the introduction of MAP-infected animals, especially in herds where disease has already been eradicated and preservation of the health status is required to maintain the PTB certification level.